Краевые задачи для интегральных уравнений с вырожденным ядром - Журавлев, В.Ф. (Нелінійні коливання, 2012)
Розглянуто крайовi задачi для iнтегральних рiвнянь з виродженим ядром. За допомогою псевдооберненого оператора отримано умови iснування та зображення єдиного розв’язку вихiдного iнтегрального рiвняння, а також умови iснування та зображення розв’язку крайової задачi для цього рiвняння. Результати проiлюстровано прикладами. We consider boundary-value problems for integral equations with degenerate kernels. By using the pseudoinverse operator, we find conditions for existence of a unique solution of the integral equation, as well as a representation for this solution. We also find conditions for existence of a solution of the boundaryvalue problem for this equation and give a representation of this solution. The results are illustrated with examples.